2022
DOI: 10.1073/pnas.2119593119
|View full text |Cite
|
Sign up to set email alerts
|

rDNA array length is a major determinant of replicative lifespan in budding yeast

Abstract: Significance Genes encoding ribosomal RNA (rDNA) are organized into a repetitive array in eukaryotic genomes. The copy number of these genes often varies and is responsive to genetics and environment. Here, we show that variation in copy number at the rDNA locus is capable of altering replicative lifespan in yeast. These results indicate that considering rDNA copy number, and conditions that could potentially change this dynamic chromosome locus, is critical for evaluating lifespan. We propose that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 57 publications
(116 reference statements)
1
17
1
Order By: Relevance
“…Our results show that the bottleneck effect is very mild because it delays by less than 1 the number of generations required to obtain the final 220 repeat number (Model A3, Fig 2B and 2C ). Then we analyzed the effect of limiting the number of replications that a mother yeast cell can make because the aging of the mother limits the number of allowed generations [ 15 , 32 ]. We found that no changes in predictions happen when this feature is taken into account (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results show that the bottleneck effect is very mild because it delays by less than 1 the number of generations required to obtain the final 220 repeat number (Model A3, Fig 2B and 2C ). Then we analyzed the effect of limiting the number of replications that a mother yeast cell can make because the aging of the mother limits the number of allowed generations [ 15 , 32 ]. We found that no changes in predictions happen when this feature is taken into account (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of this kind of autoregulated circuits has obviously been driven by natural selection, but not to necessarily allow deterministic evolution. Such a circuit has most likely evolved because it allows the efficient regulation of physiological responses, such as the adaptation of the rDNA copy number to the yeast cell volume for optimal RNA pol I transcription and genome integrity [13][14][15][16]. The circuit can, however, be activated by unusual circumstances (e.g.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the link between mitochondrial dysfunction and senescence is supported across studies, but nucleolar changes are more variable across experimental systems and the importance and timing of rDNA instability remains to be clarified. A major contributor to these differences may be variation in rDNA copy number between strains, which changes during routine yeast transformation and influences both lifespan and rDNA recombination rate (Hotz et al, 2022; Kwan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…1a). Most eukaryotic genomes harbor dozens or hundreds of rDNA copies arranged in one or multiple loci 5 , and it is well established that rDNA copy numbers vary widely even among individuals of a single species, contributing to phenotypic diversity [6][7][8][9][10] . By contrast, but how much rDNA sequences vary within a genome remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%